3x(x-1)=2(x-1)用因式分解法解列方程
来源:学生作业帮助网 编辑:六六作业网 时间:2025/02/07 12:26:51
3x(x-1)=2(x-1)用因式分解法解列方程3x(x-1)=2(x-1)用因式分解法解列方程3x(x-1)=2(x-1)用因式分解法解列方程3x(x-1)=2(x-1)3x²-3x=2x
3x(x-1)=2(x-1)用因式分解法解列方程
3x(x-1)=2(x-1)用因式分解法解列方程
3x(x-1)=2(x-1)用因式分解法解列方程
3x(x-1)=2(x-1)
3x²-3x=2x-2
3x²-5x+2=0
(3x-2)(x-1)=0
3x-2=0,x-1=0
所以x=2/3或x=1
(3x-2)(x-1)=0
x=2/3或x=1
3x(x-1)=2(x-1) (3x-2)(x-1)=0 x=1或x=2/3
(3x-2)(x-1)=0
x=1 or x=2/3
3(2X+1)=X(X+1) 用因式分解法解方程.必须用因式分解法.3(2X+1)=X(X+1) 用因式分解法解方程.必须用因式分解法.
(2x-1)(x+1)=(3x+1)(x+1) 用因式分解法
用因式分解法解(2x+3)(x+1)=(x+1)(x+3)
用因式分解法解方程:4x(2x+1)=3(2x+1)
x(2x-1)=3(1-2x)用因式分解法怎么解
用因式分解法解方程:(2x-1)(3x-4)=2x-1
3x(x-1)=2(x-1)用因式分解法
3x(x-1)=2(x-1)用因式分解法解列方程
3x(x-1)=2(x-1)用因式分解法解,
用因式分解法(1)(2x-1)²=6x²-3x
用因式分解法解方程 2x(5x-1)=3(5x-1)
用因式分解法解.3x(x-1)=2(x-1),
用因式分解法解一元二次方程(x-1)(x+2)=3(x+2)
用因式分解法解方程:3x(x-1)+2x=2
用因式分解法解方程:(2x-1)(3x+4)=2x-1.
用因式分解法解方程3x(5x+1)=10x+2
X²-3X+1=0用因式分解法 5X²+2X-1=0用因式分解法
(x+5)方+3(x+5)-4=0用因式分解法 9(x-1)方=(2x+1)方 用因式分解法